Tourism and poverty: an analysis of the data envelope for municipalities in Mexico - Kido-Cruz, Antonio; Cruz-Pérez, Juan Pablo; Ortiz Zavala, Alberto (Unidad Editorial UPTC, 2021)
Abstract This paper sought to estimate the relationship between tourism efficiency and poverty levels in municipalities monitored by the Federal Tourism Secretariat in Mexico. To calculate technical efficiency, tourism supply variables such as the number of available hotel rooms and demand variables such as the number of rooms occupied, the number of tourists and the average stay will be used through the analysis of the data envelope. Afterwards, a regression analysis was generated between tourism efficiency and income poverty levels reported by the National Evaluation Council (CONEVAL). The results show that the most efficient municipalities are Puerto Vallarta, El Fuerte and Bahía de Banderas. The least efficient are Playas de Rosarito, Tequisquiapan and Palenque. Regarding poverty and tourism efficiency, no relationship was found within the range of data analyzed. Keywords: Tourism, poverty, inequality, DEA, Mexico. JEL codes: C14 Received: 15/01/2021. Accepted: 25/07/2021. Published: 01/12/2021.